Nonadditive Gene Expression in Diploid and Triploid Hybrids of Maize - Auger, Donald L. (Genetics Society of America, 2005)
The molecular basis of hybrid vigor (heterosis) has remained unknown despite the importance of this phenomenon in evolution and in practical breeding programs. To formulate a molecular basis of heterosis, an understanding of gene expression in inbred and hybrid states is needed. In this study, we examined the amount of various transcripts in hybrid and inbred individuals (B73 and Mo17) to determine whether the quantities of specific messenger RNAs were additive or nonadditive in the hybrids. Further, we examined the levels of the same transcripts in hybrid triploid individuals that had received unequal genomic contributions, one haploid genome from one parent and two from the other. If allelic expression were merely the additive value in hybrids from the two parents, the midparent values would be observed. Our study revealed that a substantial number of genes do not exhibit the midparent value of expression in hybrids. Instead, transcript levels in the diploid hybrids correlate negatively with the levels in diploid inbreds. Although transcript levels were clearly nonadditive, transcript levels in triploid hybrids were affected by genomic dosage.